Broadlands and the new rurality : an ethnography - Hillyard, Sam (Emerald Publishing Limited, 2020)
In this ethnographic study of the rural idyll, Broadlands explores rurality and the pace of rural life. In sharp contrast to the urban analytical emphasis upon speed, it gives careful thought to stasis, as rural places offer everyday opportunities for very different social situations and behavioural interactions. Based on new and extensive RCUK-funded primary research, Sam Hillyard generates an original, rigorous and thoughtful understanding of everyday rural life in the 21st century. Taking the principles of dramaturgy and rural studies scholarship, Broadlands provides a toolkit to make sense of rural change. It uses ethnography to enhance interactionist dramaturgy via cross-references with new theoretical orientations that emphasise the temporal dynamics of space in a 'knowing capitalism'. Where early dramaturgy stressed formal organisations in shaping roles and identity, Broadlands expands these concepts to include informal and transient organisations and associations. Ultimately, the book advances a new model for grasping the complexity of the rural. For researchers and students of rural and urban sociology, this is an engaging text that reframes our understanding of rurality.
Introduction 1. Thinking about rurality -- 2. Norfolk: the agrarian revolution and the emergence of an elite -- 3. Patterns of ownership in modernity 4. -- A village of three parts -- 5. Village institutions #1: The school, the pub and the church -- 6. Village institutions #2: The very model of a modern rural villager -- 7. A tale of three villages: Norfolk, 'economy' Norfolk and Northants -- 8. Methodological note -- Conclusion.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Sociology, Rural; Ethnology; Rural conditions; Social Science -- Sociology -- Rural; Rural communities